Urea(lly) Got Me: An Uncommon Etiology of Peripartum Liver Failure. Issue 5 (20th May 2022) - Spiller, Robert E.; Colombo, Christopher J.; Lindholm, Phillip C.; Kwon, James
ABSTRACT: A 23-year-old woman presented 4 days postpartum for agitation and confusion, with initial evaluation consistent with acute fatty liver of pregnancy (AFLP). Later in her course, an amino acid panel was highly suggestive of citrullinemia type 1. She was started on arginine supplementation and glycerol phenylbutyrate and evaluated for a liver transplant. After starting the medication and diet modification, her liver failure resolved, and she was safely discharged. Urea cycle disorders may mimic AFLP with liver enzyme elevation, delirium, and hyperammonemia, but unlike AFLP, patients with urea cycle disorders will typically not recover without dietary modifications and/or medication.